O fracasso da Comissão Mista Brasil-Estados Unidos (CMBEU) e os rumos da política econômica no segundo governo Vargas (1951-54) - Lopes, Marcio Augusto Falcão (2009)
This dissertation aims to introduce the essential characteristics of the constitution of Joint Comission Brazil-USA (CMBEU) which agreement was signed in 1950, December, still in the course of the president Dutra governement (1946-1950). The beginning of the CMBEU tecnical works happened in 1951, July, already in the course of the second Vargas government. This commission reunited Brazilian and North-American technicians and elaborated 41 projects which had the goal to eliminate the bottlenecks in the infrastructure and industry. These project s financing which values approximated US$ 390 millions would be disposed from multilateral institutions as the Eximbank and the BIRD, besides about Cr$ 14 billions (about US$ 690 millions) to be captivated internally. The ascension to the presidency of the United States by the Republican Eisenhower in 1953 concomitant to other reasons to be introduced in this work would represent the end of the CMBEU works and as consequence the interruption of the financing of the elaborated projects. The dissertation searchs to analyze the course of the economic policy in the second Vargas government focused mainly the period after the end of the CMBEU works which importance to the Brazilian Economy pretends to be analysed